General Ailments Related with Agnidushti (AYUSHDHARA, 2023)
Agni is described as an important factor of digestion and metabolism in Ayurveda treatise. Agni is responsible for all the vital functions within body and determines the quantity of food to be consumed. The conversion of ingested food in the form of energy through digestion, absorption and assimilation completely depend upon individual’s Agni i.e., digestive fire. Agni has a significant role in balanced body functioning and keeping the body components in homeostasis. According to Acharya Charak, Dehagni is considered as the cause of life, complexion, strength, lustre, health sustenance, Oja, Teja and it shows the critical importance of Agni in overall health of an individual. Individuals die when their Agni stops working, but when their Agni is Sama (balanced), they are completely well and live a long, happy, and healthy life. When a person’s Agni is vitiated, his entire metabolism is disrupted resulting in bad health and disease. As a result Agni is considered the foundation (Mool) of life. Although the number of Agni in our body is uncountable because it play an important role in metabolism even at cellular or molecular level particularly then also in Ayurvedic texts it mainly considered of 13 types in number. These are one Jatharagni or Koshthagni, five Bhootagni and seven Dhatvagni. Firstly, Jatharagni perform its action in Koshtha (stomach) then Bhootagni and Dhatvagni perform their action. Any kind of disturbance at any level of digestion and metabolism (Aaharpachankriya) leads to certain kind of disruption in normal functioning of Agni. It may be hyper or hypo or fickle state of Agni (Tikshnagni, Mandagni, Vishamagni). These all conditions called as Agnidushti. Agnidushti is a common cause for general health ailments like Ajeerna (indigestion), Amlpitta (acidity), Atisaar (diarrhoea), Arsha, Grahani (IBS or IBD) etc. Consumption of unhealthy food without following the Aaharvidhi described in Ayurvedic texts increasing these health issues day by day. The paper is about to deciphering these ailments in respect with pathogenesis i.e., Samprapti.